2006
DOI: 10.1002/ptr.1859
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of several herbal extracts on avian peripheral blood cell immune responses

Abstract: Standardized ethanol extracts of Allium sativum (garlic), Glycyrrhiza glabra (licorice), Plantago major (plantain) and Hippophae rhamnoides (sea buckthorn) were assessed for their effects on cellular immunity in laying hens. Birds (n = 25) had blood samples taken and both specific and non-specific immune cell responsiveness were evaluated by a leukocyte proliferation assay, carbon clearance test and SRBC phagocytosis in monocyte-derived macrophage cultures. Licorice and sea buckthorn (50 microg/mL) clearly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 29 publications
1
28
1
1
Order By: Relevance
“…The positive effect of feeding plant extracts on immune responses is in agreement with literature. Ethanol extracts of Allium sativum (garlic), Glycyrrhiza glabra (licorice), Plantago major (plantain) and Hippophae rhamnoides (sea buckthorn), which are containing PC, had some beneficial effects on cellular immunity in laying hens (Dorhoi et al., ). The phagocytic activity of peripheral blood leucocytes in chickens orally administered sugar cane extracts or a polyphenol‐rich fraction of the sugar cane extract (500 mg/kg) for three consecutive days increased significantly, when compared with that of saline‐administered control chickens (Hikosaka et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of feeding plant extracts on immune responses is in agreement with literature. Ethanol extracts of Allium sativum (garlic), Glycyrrhiza glabra (licorice), Plantago major (plantain) and Hippophae rhamnoides (sea buckthorn), which are containing PC, had some beneficial effects on cellular immunity in laying hens (Dorhoi et al., ). The phagocytic activity of peripheral blood leucocytes in chickens orally administered sugar cane extracts or a polyphenol‐rich fraction of the sugar cane extract (500 mg/kg) for three consecutive days increased significantly, when compared with that of saline‐administered control chickens (Hikosaka et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Their positive effect is demonstrated mainly on growth and egg productive performance, quality egg traits, differencial blood count and immunity response (Dorhoi et al, 2006;Canogullari et al, 2009Canogullari et al, , 2010Ghasemi et al, 2010;Mohebbifar and Torki, 2010;Navid et al 2014). There are many evidence to suggest that they may have beneficial influence on useful gut microflora altogether with inhibitory effects on pathogenic and conditionally pathogenic bacteria -clostridia, colibacteria, salmonellae etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently studies have shown that sea buckthorn has antioxidant (Geetha et al, 2002a; Geetha et al, 2002b; Chawla et al, 2007; Püssa et al, 2007; Geetha et al, 2009), anticancer (Olsson et al, 2004; Ma et al, 2007; Boivin et al, 2007), antiinfective (Larmo et al, 2008) and exerts beneficial effects on liver fibrosis (Gao et al, 2003) and immune function (Dorhoi et al, 2006). Sea buckthorn decreases the damage of enzyme activity or hormonal metabolic organism status caused by immobilization or cold-hypoxia-restraint (Krylova et al, 2000; Saggu and Kumar, 2007), however, its effects on heat stress is unclear.…”
Section: Introductionmentioning
confidence: 99%